A textbook as a motivational means in the Serbian language teaching - Stakić Mirjana M.; Čutović Mirjana M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2017)
We examine the content of the textbook for the fourth grade of the primary school as a motivational means in the function of learning the Serbian language. The aim is to define the teachers' opinions about: 1) whether the content in the textbook motivates students to explore and independently learn; and 2) whether the contents in the textbook refer students to internal and interrelated correlation between subjects. The survey was conducted in 2016 on the sample of 153 teachers. The results, in the opinion of the teachers, suggest that the contents in the textbook do not greatly encourage students to research and learn independently and do not refer them to a large extent the to the internal and interrelated correlation between subjects. The complex and meaningfully rich structure of the literary text enables them to make numerous parallels and relations between the meaningful strata of the text both with the students' life experience, as well as with their knowledge from other subjects and grammar. The above implies that it is necessary to improve the quality of the textbook in the segment of the methodical apparatus used in the analysis and interpretation of literary texts. A qualitative change in the structure of the textbook would concern improvements in the methodical apparatus of the learner's motivation for learning (research and independent work), and making correlation of literature teaching with both grammar teaching and the curriculum content of other subjects.